Molecular Characterization of Microbiota Associated With Sperm of Malaysian Mahseer Tor tambroides. (June 2019) - Koh, Ivan Chong Chu; Badrul Nizam, Bin Hassan; Muhammad Abduh, Yazid; Abol Munafi, Ambok Bolong; Iehata, Shumpei
Malaysian Mahseer ( Tor tambroides ) is considered as a good prospect for aquaculture in Malaysia. However, knowledge about Malaysian Mahseer-associated sperm microbiota is still limited, although some studies reported that sperm-related bacteria are a factor in the decline of sperm quality, as sperm may become the carrier of pathogenic bacteria to the egg. The goal of this study was to evaluate the sperm microbiota associated with Malaysian Mahseer from 3 different locations (Universiti Malaysia Terengganu [UMT], Ajil, and Pahang) using polymerase chain reaction denaturing gradient gel electrophoresis (PCR-DGGE) fingerprinting and to compare location differences by cluster analysis. Our results showed that the UMT sample had different sperm microbiota composition and a different trend in its relationship with sperm quality. Correlation analysis showed a relationship between bacterial diversity and sperm quality. Phylogenetic analysis indicated that sperm microbiota was composed of diverse phyla, including Proteobacteria, Firmicutes, and Actinobacteria. Interestingly, bacteria such as Salinisphaera sp., Pelomonas sp., and Staphylococcus spp. were detected in all the locations, suggesting that these bacteria are indigenous bacterial members of the Malaysian Mahseer sperm microbiota, although their function is still unclear.